Economic impact of a peste des petits ruminants outbreak and vaccination cost in northwest Ethiopia - Jemberu, Wudu T.; Knight-Jones, Theodore J.D.; Gebru, A.; Mekonnen, S.A.; Yirga, A.; Sibhatu, D.; Rushton, J. (Hindawi Limited, 2022)
Peste des petits ruminants (PPR) is an important endemic disease of small ruminants in Ethiopia. While vaccination is widely used in the country to control the disease, quantitative estimates of the actual economic losses due to outbreaks and costs of vaccination are scarce. This study assessed the economic impact and costs of vaccination of PPR in Metema district, northwest Ethiopia. The economic impact of the disease was estimated from outbreak investigation including interviews with 233 smallholder farmers in PPR affected kebeles (sub-districts). The cost of PPR vaccination was obtained from vaccination programs in six kebeles of the district and from secondary data from the district veterinary office. In the investigated PPR outbreak, animal level PPR morbidity and mortality rates were, respectively, 51% and 22% in sheep and 51% and 25% in goats. The flock level morbidity rate was 83% for sheep flocks and 87% for goat flocks. The mean flock level loss was Ethiopian Birr (ETB) 7835 (USD 329 in 2018 average exchange rate) (95%CI: 5954 - 9718) for affected sheep flocks and ETB 7136 (USD 300) (95%CI: 5869–8404) for affected goat flocks. The losses in all study flocks during the outbreak were ETB 319 (USD13.4) per sheep and ETB 306 (USD12.9) per goat. Mortality accounted for more than 70% of the total losses in both sheep and goat flocks. Vaccination costs for PPR were estimated at ETB 3 per correctly vaccinated animal. Based on the estimated animal-level direct economic losses and vaccination cost, it can be conjectured that vaccination will pay if a district PPR outbreak occurs more than once every 13 years. This does not account for additional benefits from vaccine-derived herd immunity reducing disease burden in the wider population. In conclusion, PPR caused high morbidity and mortality in the affected flocks and resulted in high economic losses, equivalent to 14% of annual household income, dramatically affecting the livelihoods of affected flock owners. The vaccination practised in the district is likely to have a positive economic return with strengthened vaccination programs bringing reduced economic impact and improved livelihoods.